Artificial Intelligence in Modern Higher Education (Literature Review and Results of Teacher Pilot Testing) - Filipov , Olgerd (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The publication examines the issue of implementing artificial intelligence in higher education within the context of digital humanism. The aim of the study is to identify how teachers perceive the opportunities, risks, and regulatory conditions of using AI in higher education based on a review of modern publications and an analysis of pilot testing results. The theoretical basis of the study is the works on digital humanism, algorithmic justice, the quality of digital higher education, and the institutional conditions for implementing AI. The empirical foundation was the results of a pilot survey of non-state university teachers, which concluded that a humanistic-oriented model of AI implementation, involving human control, data protection, transparent rules, teacher and student participation in regulatory development, as well as the development of digital and ethical competence, is fundamentally important for higher education.